Characterization of Phonons in Molecular Crystals - Singh, R.; George, D.; Markelz, A. G. (Frontiers in Optics 2010, 2010)
We demonstrate a new technique for characterizing the phonons in molecular crystals, Modulated Orientation Sensitive Terahertz Spectroscopy (MOSTS). The technique suppresses crystal defects and solvent contributions, and enhances contributions due to molecular structure and anisotropy.